1992
DOI: 10.1111/j.1600-0773.1992.tb00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Breathing Zone Concentrations of Methylmethacrylate Monomer During Joint Replacement Operations

Abstract: By use of a methylmethacrylate (MMA) Dräger tube and bellow bump, the breathing zone concentrations of MMA monomer were measured for the operating surgeon during cementation of the components of hip and knee joint prostheses. The highest recordings (50-100 p.p.m.) were encountered during cementation of the acetabular cups with conventional polymethylmethacrylate cement. Such exposure could be eliminated by the use of personal protection equipment, local punctual field suction or change to a MMA/n-decylmethacry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 4 publications
(3 reference statements)
0
12
0
Order By: Relevance
“…Interestingly, little information has been published to date regarding exposure of the scrub nurse to MMA fumes during vacuum mixing or handmixing of bone cement. Former studies concentrated more on monomer detection during handmixing and found values from 200-500 ppm at a maximum distance of 10 cm from the bowl (Darre et al 1988a), whereas cementing of the actetabular component is known to cause concentrations of 50-100 ppm in the breathing zone of the surgeon (Darre et al 1992). Another study found MMA concentrations of 87 ppm when measuring over a period of 10 min next to a Vacu-Mix System (Darre et al 1988a).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, little information has been published to date regarding exposure of the scrub nurse to MMA fumes during vacuum mixing or handmixing of bone cement. Former studies concentrated more on monomer detection during handmixing and found values from 200-500 ppm at a maximum distance of 10 cm from the bowl (Darre et al 1988a), whereas cementing of the actetabular component is known to cause concentrations of 50-100 ppm in the breathing zone of the surgeon (Darre et al 1992). Another study found MMA concentrations of 87 ppm when measuring over a period of 10 min next to a Vacu-Mix System (Darre et al 1988a).…”
Section: Discussionmentioning
confidence: 99%
“…In a 1992 investigation Darre et al measured air concentrations of MMA within the breathing zone of the surgeon during live total knee and total hip arthroplasties [23]. The use of a surgical helmet system was found to completely eliminate MMA vapor.…”
Section: Discussionmentioning
confidence: 98%
“…However, the characteristic smell of MMA, which can be detected at a concentration as low as 0.2 ppm, was still evident 9 . Darre et al measured an MMA concentration of 50 to 100 ppm in the breathing zone of a surgeon performing hip arthroplasty; however, use of a surgical helmet or local surgical field suction reduced this to an undetectable level 10 . In a similar study, Cloft et al measured the concentration of MMA vapor during percutaneous vertebroplasty 11 .…”
Section: Potential Occupational Hazardsmentioning
confidence: 99%